Analysis of the cellular immune responses to vaccines - Svitek, Nicholas; Taracha, E.L.N.; Saya, Rosemary; Awino, Elias; Nene, Vishvanath M.; Steinaa, Lucilla (Springer, 2022)
Flow cytometry, enzyme-linked immunospot (ELISpot), and cellular cytotoxicity assays are powerful tools for studying the cellular immune response toward intracellular pathogens and vaccines in livestock species. Lymphocytes from immunized animals can be purified using Ficoll-Paque density gradient centrifugation and evaluated for their antigen specificity or reactivity toward a vaccine. Here, we describe staining of bovine lymphocytes with peptide (p)-MHC class I tetramers and antibodies specific toward cellular activation markers for evaluation by multiparametric flow cytometry, as well as interferon (IFN)-γ ELISpot and cytotoxicity using chromium (51Cr) release assays. A small component on the use of immunoinformatics for fine-tuning the identification of a minimal CTL epitope is included, and a newly developed and simple assay to measure TCR avidity.